THE IMPACT OF SOCIAL MEDIA ON ADOLESCENTS' COMMUNICATION PATTERNS - Aldiawan, Aldiawan; Suharto, Suharto (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2025)
Social media has become an integral part of adolescents' lives and has a significant impact on their communication patterns. This study aims to examine the impact of social media use on adolescent communication patterns, both from positive and negative sides. This study uses a descriptive qualitative method with a literature study approach. Data was collected through the review of various literature sources in the form of books, scientific journals, articles, and online sources relevant to the research topic. The results of the study show that social media has a positive impact in the form of ease of communication, expansion of social networks, increased access to information, and support for adolescent self-development. However, uncontrolled use of social media also has negative impacts, such as decreased quality of face-to-face communication, low social empathy, mental health disorders, decreased learning achievement, and the risk of behavioral deviations. Therefore, the active role of parents and educators is needed in providing assistance, supervision, and digital literacy education so that adolescents are able to use social media wisely, responsibly, and in a balanced way in their social lives.